127k views
0 votes
3 ln x = ln 16 + ln 4. Solve for x.

Please walk me through which log rule to use once you get to the point:
ln x = (ln 16 + ln 4)/3

2 Answers

2 votes

Explanation:

See the picture for steps

3 ln x = ln 16 + ln 4. Solve for x. Please walk me through which log rule to use once-example-1
User Kim HJ
by
5.6k points
3 votes

Answer:

4

Explanation:


ln(x) = ln(16) + ln(4)

Use the Produxt Rule


ln(a) + ln(b) = ln(a + b)

Remeber that Ln is a log function with base e,

so know we have


3 ln(x) = ln(64)


ln(a) = ln(b)

Only if a=b So we have

x^3=64

x=4


x = 64

User Ashkan S
by
5.9k points